2019
DOI: 10.1002/ijc.32410
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic cooperation between auranofin, a thioredoxin reductase inhibitor and anti‐PD‐L1 antibody for treatment of triple‐negative breast cancer

Abstract: Triple‐negative breast cancer (TNBCs) is a very aggressive and lethal form of breast cancer with no effective targeted therapy. Neoadjuvant chemotherapies and radiotherapy remains a mainstay of treatment with only 25–30% of TNBC patients responding. Thus, there is an unmet clinical need to develop novel therapeutic strategies for TNBCs. TNBC cells have increased intracellular oxidative stress and suppressed glutathione, a major antioxidant system, but still, are protected against higher oxidative stress. We sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…Gold compounds exert cytotoxic effects by inhibiting thiol-containing enzymes, especially TrxR (Liu and Gust, 2013 ; Ortego et al, 2014 ; Bian et al, 2019 , 2020a , b ; Fan et al, 2019 ), damaging mitochondrial (Rigobello et al, 2002 ; Rackham et al, 2007 ) and DNA function (Messori et al, 2005 ; Patel et al, 2013 ), all of which may contribute to their clinical anticancer activity. Recently, many groups have found that auranofin, a gold compound widely used in antirheumatic therapy (Sadler and Sue, 1994 ; Shaw, 1999 ), also has anticancer, antibacterial and other properties (Marzano et al, 2007 ; Fiskus et al, 2014 ; Harbut et al, 2015 ; Diez-Martinez et al, 2016 ; Thangamani et al, 2017 ; AbdelKhalek et al, 2019 ; Onodera et al, 2019 ; Raninga et al, 2020 ). Therefore, there is growing interest in the investigation of gold compounds with new applications.…”
Section: Introductionmentioning
confidence: 99%
“…Gold compounds exert cytotoxic effects by inhibiting thiol-containing enzymes, especially TrxR (Liu and Gust, 2013 ; Ortego et al, 2014 ; Bian et al, 2019 , 2020a , b ; Fan et al, 2019 ), damaging mitochondrial (Rigobello et al, 2002 ; Rackham et al, 2007 ) and DNA function (Messori et al, 2005 ; Patel et al, 2013 ), all of which may contribute to their clinical anticancer activity. Recently, many groups have found that auranofin, a gold compound widely used in antirheumatic therapy (Sadler and Sue, 1994 ; Shaw, 1999 ), also has anticancer, antibacterial and other properties (Marzano et al, 2007 ; Fiskus et al, 2014 ; Harbut et al, 2015 ; Diez-Martinez et al, 2016 ; Thangamani et al, 2017 ; AbdelKhalek et al, 2019 ; Onodera et al, 2019 ; Raninga et al, 2020 ). Therefore, there is growing interest in the investigation of gold compounds with new applications.…”
Section: Introductionmentioning
confidence: 99%
“…Auranofin significantly suppressed NONO and both the STAT3 mRNA and protein expression level in MDA-MB-231 cells (Figure 7 C-E). The murine 4T1.2 syngenic model reflecting TNBC phenotypes 41 and the xenograft model using MDA-MB-231 revealed that NONO expression was decreased by auranofin treatment (Figure 7 F). To next whether the cell growth inhibition by auranofin is dependent on NONO gene expression, we performed a rescue experiment.…”
Section: Resultsmentioning
confidence: 98%
“…Auranofin is a well-known anti-inflammatory drug used in rheumatoid arthritis 54 . Recently, several studies based on a drug-repositioning concept have suggested that auranofin possesses anti-proliferative effects in cancer cells 41 . Although our current results hint to auranofin being able to modulate NONO activity, other and more specific targeting agents will also need to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of the high cytotoxicity of MNP-DHA, we tried to use this combination to conduct toxicity experiments on other canonical lethal breast cancer cell lines that were triple negative (MDA-MB-231) and human epidermal growth factor receptor (HER2) overexpressing (MDA-MB-453) (Neve et al, 2006;Lee et al, 2012). Triple-negative breast cancer, defined by the lack of estrogen receptor, progesterone receptor and HER2, frequently developed resistance to chemotherapy over long-term treatment (Kim et al, 2018;Raninga et al, 2020). HER2 was overexpressed in 25-30% of breast cancers which was a considerable proportion, and patients with breast cancers that overexpress HER2 had much lower overall survival and disease-free survival due to high metastasis (Baselga et al, 1998;Slamon et al, 2001;Büyükköroglu et al, 2016).…”
Section: Cytotoxicity Assays Of Other Breast Cancer Cellsmentioning
confidence: 99%